Analysis Of Village Direct Cash Assistance (BLT) Program Evaluation In An Effort To Improve Community Welfare In The Village Of Simpang Kiri, Tenggulun District, Aceh Tamiang Regency: - - Rossevelt, Franklin Asido (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Village funds are funds sourced from the APBN which are distributed to villages and transferred to village accounts. Village funds are used for organizing and implementing community development and empowerment. Covid-19 entered Indonesia in early 2020 which had an impact on the decline in the economy of both the country and its people. This resulted in people coming from the middle to lower economy increasingly difficult to meet their daily needs. Therefore, government assistance is needed in meeting the obligatory needs of the community. The method used in this research is descriptive method. The data collection technique is done by conducting interviews and documentation. The research location was carried out in Lestari Dadi Village, Pengajahan District, Deli Serdang Regency. The focus of this research is the evaluation of BLT Dana Desa. Globally, the problem regarding BLT village funds is related to the community receiving assistance. From the evaluation, the distribution of Village BLT Funds in Lestari Village was not on target, as a result, it was found that people who received assistance were not on target, namely Village Fund BLT recipients who were still classified as capable.